Foreign aid and its effectiveness - Erlichová, Linda (2010)
Purpose of this diploma thesis is to analyze foreign aid as a stabile part of nations expenditures of all developed countries since 60's. But at the same time foreign aid not being important enough for developed countries to manage it more effectively. This diploma thesis analyses among others development of different economic approaches on this topic, financial flows of this sort since the beginning and also an analysis of foreign aid as whole as well as some of its parts. I`m also trying to find reasons why developed nations provide foreign aid and also motives for accepting it by developing nations. Also trade liberalisation is described as the only way of solving foreign aid poor effeciency.